Pressure cells for in situ neutron total scattering: time and real‐space resolution during deuterium absorption. Issue 6 (1st December 2022) - Ikeda, Kazutaka; Ohshita, Hidetoshi; Otomo, Toshiya; Sakaki, Kouji; Kim, Hyunjeong; Nakamura, Yumiko; Machida, Akihiko; Von Dreele, Robert B.
Abstract : In situ gas‐loading sample holders for two‐dimensionally arranged detectors in time‐of‐flight neutron total scattering experiments have been developed for the structural analysis of the deuterium absorption process using time and real‐space resolution. Abstract : In situ gas‐loading sample holders for two‐dimensionally arranged detectors in time‐of‐flight neutron total scattering experiments have been developed to investigate atomic arrangements during deuterium absorption using time and real‐space resolution. A single‐crystal sapphire container was developed that allows conditions of 473 K and 10 MPa hydrogen gas pressure. High‐resolution transient measurements detected deuterium absorption by palladium that proceeded within a few seconds. A double‐layered container with thick‐ and thin‐walled vanadium allowed conditions of 423 K and 10 MPa hydrogen gas pressure. The deuterium occupation sites of a lanthanum–nickel–aluminium alloy are discussed in detail on the basis of real‐space high‐resolution data obtained from in situ neutron scattering measurements and reverse Monte Carlo structural modeling.